2013
DOI: 10.1007/s00467-013-2574-9
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 receptor staining in pediatric idiopathic membranous glomerulopathy

Abstract: PLA2R staining sensitivity is much lower in the pediatric than the adult primary membranous glomerulopathy population. This finding suggests a more diverse and currently incompletely described set of etiologies for this disease in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…The results of the present study are similar to our adult PMN experience. In the study by Cossey et al 7 , 45% of the paediatric PMN cases had enhanced staining for PLA 2 R. Different study population may explain the difference. There was a very good association of aPLA 2 R with clinical response.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The results of the present study are similar to our adult PMN experience. In the study by Cossey et al 7 , 45% of the paediatric PMN cases had enhanced staining for PLA 2 R. Different study population may explain the difference. There was a very good association of aPLA 2 R with clinical response.…”
Section: Discussionmentioning
confidence: 92%
“…The study included 11 (61.11%) male and seven (38.89%) female subjects. The duration of illness was 10.11 ± 5.26 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) months. The mean proteinuria, serum albumin and serum creatinine was 4.52 ± 1.93 (2.43-9.20) g/day, 1.99 ± 0.68 (1.04-3.40) g/dL and 1.04 ± 1.67 (Median 0.70, IQR 0.48-0.82) mg/dL.…”
Section: Baseline Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to stain archival biopsy specimens for PLA 2 R has allowed an analysis of the frequency of PLA 2 R-associated disease in a pediatric population. A recent analysis in biopsies from cases ranging in age from 4 to 17 has shown that 10/22 (45%) of pediatric biopsies exhibited PLA 2 R staining in a granular capillary loop pattern; the youngest case was from a ten year-old [49]. Those cases negative for PLA 2 R had more evidence of secondary features, such as mesangial deposits, the presence of C1q, and predominance of an IgG subclass other than IgG4.…”
Section: Pla2r-associated Mnmentioning
confidence: 99%
“…Cossey et al . evaluated staining for PLA2R in glomerular deposits in 22 patients with IMN between the ages of 4 and 17 years, and noted positivity in 45% of cases . The frequency of anti‐PLA2R positivity in the paediatric population has not been studied.…”
mentioning
confidence: 99%